The influence of sources and solid phase extraction criteria on dissolved organic matter optical properties in aquatic systems - Chuang, Chia-Ying Anderin; Ho, Yun-Hsuan (Frontiers in Marine Science, 2023)
The integrity of studies investigating the composition of dissolved organic matter (DOM) is heavily dependent on the sampling and instrumental techniques employed. In this study, we aimed to assess the impacts of both the source of the DOM and the solid phase extraction (SPE) criteria on changes to the optical properties of DOM. Samples were collected from various aquatic environments, ranging from headwaters to the open ocean. The extraction kinetics of DOM were monitored throughout the SPE process, with alterations to the DOM verified using optical properties derived from chromophoric dissolved organic matter (CDOM), including absorbance and fluorescence measurements. The fluorescence excitation-emission matrices (EEMs) were further analyzed using PARAllel FACtor analysis (PARAFAC) to resolve the underlying chemical components. Results indicate that the reaction of DOM to acidification required for polystyrene-divinylbenzene polymer sorbent SPE varies across samples. And this variability may stem from differences in functional groups and DOM sources. The maximum carbon loading observed was 9.7 mg C per 1 g PPL, which is a widely used styrene-divinylbenzene polymer sorbent, and no overloading was noted. The dissolved organic carbon (DOC) extraction efficiency (EE) ranged from 51.5-61.5% and 27.6-40.0% for post- and extract- calculations, respectively, with no significant differences in DOC EE observed among different initial DOC concentrations, salinities, and flowrates. The differences in DOC EE across diverse sources and changes in optical proxies resulting from PPL extraction were mainly due to the heterogeneity of DOM. PPL extraction altered the overall molecular characteristics of DOM from more labile to more refractory or degraded in the open ocean and headwater source samples. Notably, high and low flowrates yielded identical SPE-DOM extraction and alterations. The results indicate that DOM sources primarily control SPE EE rather than methodological or other environmental factors. PPL SPE results in a convergence of DOM variability. These findings provide crucial insights into inter-study comparisons and the interpretability of SPE-derived DOM data from samples across diverse aquatic environments.